Value Chain Analysis of Honey in Bangladesh: Production Practices and Livelihood Perspective - Uddin, MT; Kamal, MZI; Kamruzzaman, M (SAARC Journal of Agriculture, 2022)
The study was designed to develop honey value chain through analyzing the production practices and stakeholders’ activities as mediated by livelihood strategies. A total of 84 stakeholders were interviewed for data collection. The study depicts that assemble and set up the wooden box with artificial wooden beehives near the fields was the main procedure for honey production. Apis melifera is the major honey bee reared by the beekeepers and the average number of boxes is 50, harvested honey per box per year is around 35 kg. Profitability analysis shows that honey production was profitable and the benefit-cost ratio is 1.83. Estimates of logit model indicates that age of household head, educational level, farm size, farm income and non-farm income were the significant factors that influence beekeepers’ decision for adoption. The study identified six actors in honey value chain and among the actors; processors added the highest value of total value addition. Engagement in different activities of beekeeping had a great impact on their livelihood. SWOT analysis indicates favorable environment as strength, inadequate market infrastructure as weakness, high demand for honey as opportunities, and dominancy of the middlemen as threat, respectively. Lack of credit, lower price of honey as well as lack of storage facilities was the main problems faced by the stakeholders. To overcome the problems moreover to make this business more profitable, the study recommended to form contract based cooperative groups, establish proper storage facilities and provide necessary training by the government and non-government organizations. SAARC J. Agric., 19(2): 301-315 (2021)